How to read water : clues and patterns from puddles to the sea : learn to gauge depth, navigate, forecast weather and make other predictions with water - Gooley, Tristan (The Experiment, 2016)
"In his eye-opening books The Lost Art of Reading Nature's Signs and The Natural Navigator, Tristan Gooley helped readers reconnect with nature by finding direction from the trees, stars, clouds, and more. Now, he turns his attention to our most abundant--yet perhaps least understood--resource. Distilled from his far-flung adventures--sailing solo across the Atlantic, navigating with Omani tribespeople, canoeing in Borneo, and walking in his own backyard--Gooley shares hundreds of techniques in How to Read Water,"--Amazon.com.